The ICJ opinion on kosovo: Symphony or cacophony? - Ahmad, Rusniah; Efevwerhan, David I. (The Indian Society of International Law, 2010)
On July 22, the ICJ delivered it s Opinion on the Kosovo unilateral declaration of independence in response to the request by the General Assembly to do so in GA Resolution 63/3 of October 8, 2008. This paper reviews the Opinion, highlighting the major aspects on self-determination and secession.It concludes that while the Court's pronouncements on territorial integrity and the non-prohibition of secession in international law are symphonic and welcome, its failure to examine and pronounce on the availability or not of the right to remedial secession, leaves a cacophony of questions to be answered in that aspect of international law.